Robust and fast selective encryption for HEVC videos - Mokhtar Ouamri (Journal of Communications Software and Systems, 2014)
Emerging High efficiency video coding (HEVC) is expected to be widely adopted in network applications for high definition devices and mobile terminals. Thus, construction of HEVC's encryption schemes that maintain format compliance and bit rate of encrypted bitstream becomes an active security's researches area. This paper presents a novel selective encryption technique for HEVC videos, based on enciphering the bins of selected Golomb–Rice code’s suffixes with the Advanced Encryption Standard (AES) in a CBC operating mode. The scheme preserves format compliance and size of the encrypted HEVC bitstream, and provides high visual degradation with optimized encryption space defined by selected Golomb–Rice suffixes. Experimental results show reliability and robustness of the proposed technique.